2022
DOI: 10.1155/2022/1054297
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Thyroid Malignancy in Patients with Toxic Nodular Goiter

Abstract: Background. Although hyperfunctioning thyroid disorders were thought to be protective against malignancy, some recent studies reported a high incidence of incidentally discovered cancer in patients with hyperfunctioning benign thyroid disorders. We performed this study to estimate the incidence and predictors of malignant thyroid disease in patients with toxic nodular goiter (TNG). Patients and Methods. The data of 98 patients diagnosed with TNG were reviewed (including toxic multinodular goiter SMNG and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Though it is often taught that toxic thyroid nodules are benign, and hyperthyroidism is correlated with a low risk of thyroid cancer, several surgical series show a higher-than-expected incidence of thyroid cancer. Mohamed et al reported a 21% malignancy rate in patients who underwent surgery with toxic multinodular goiter or toxic adenomas, though there was not specification of the presence of thyroid cancers within the autonomous thyroid tissue (9). Tam et al found a similar 19% malignancy rate in toxic nodular goiter resections with specification that half (9.5%) of these malignancies arose from the autonomous nodule/s (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it is often taught that toxic thyroid nodules are benign, and hyperthyroidism is correlated with a low risk of thyroid cancer, several surgical series show a higher-than-expected incidence of thyroid cancer. Mohamed et al reported a 21% malignancy rate in patients who underwent surgery with toxic multinodular goiter or toxic adenomas, though there was not specification of the presence of thyroid cancers within the autonomous thyroid tissue (9). Tam et al found a similar 19% malignancy rate in toxic nodular goiter resections with specification that half (9.5%) of these malignancies arose from the autonomous nodule/s (10).…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al. reported a 21% malignancy rate in patients who underwent surgery with toxic multinodular goiter or toxic adenomas, though there was not specification of the presence of thyroid cancers within the autonomous thyroid tissue ( 9 ). Tam et al.…”
Section: Introductionmentioning
confidence: 99%